Effect of green supply chain management practices on sustainability performance of ISO14001 SMEs - Qazi, Fawad Habib (2016)
Malaysia has moved from agriculture-based economy to an industrial-based economy. As a consequence, manufacturing has increased markedly over the years that results 33.9% contribution to GDP. Literature have shown that of manufacturing activities are responsible for air and water pollution, toxic emission, and chemical spills that have created environmental issues. Globalization has increased customers awareness about environmental issues that introduced business opportunities for environmentally conscious manufacturing industries. Hence, manufacturing industries are facing pressure from global market to improve their sustainability performance by implementing environmental management practices. This research aims to determine the level of Green Supply Chain Management (GSCM) practices and investigate their effect on the environmental, economic, and intangible performance. The research adapted survey research design using questionnaire to obtain data of GSCM practices from representatives of Small Medium Enterprises (SMEs) in the study area. The questionnaire was adapted from previous studies, and purposive sampling was used to select respondents. Data were collected from 120 SMEs to test the research hypothesis. The results showed that generally, there is medium implementation of GSCM practices among the studied SMEs which results improved performance. In addition, the results suggest that SMEs should strive to implement GSCM practices from the environmental point of view. Therefore, results clarify SMEs current state to assist both industry and academia on the way toward enhancing performance. It is recommended that more research should be conducted on GSCM practices and their effect on the intangible performance as limited studies were found on this aspect.